Starting and Maintaining 4-H Clubs - Joy Jordan; Bryan Terry; Dale Pracht; Judy Butterfield; Adam Cletzer (EDIS)
This revised 16-page guide, intended for 4-H staff and volunteers, provides an overview of the types of clubs, the criteria and forms for chartering a new club, and for maintaining club status annually. It also outlines the fiscal responsibilities of club management and the standards for recognition. Written by J. Jordan, B. Terry, D. Pracht, J. Butterfield, and A. Cletzer, and published by the UF Department of 4-H Youth Development, March 2012.